2002
DOI: 10.1037/0021-9010.87.6.1191
|View full text |Cite
|
Sign up to set email alerts
|

The disclosure dilemma for gay men and lesbians: "Coming out" at work.

Abstract: This study examined disclosing sexual orientation at work for 220 gay men and 159 lesbians. Self-acceptance, the centrality of one's identity, how "out" one is to friends and family, employer policies, and perceived employer gay-supportiveness were associated with disclosure behaviors at work for gay/lesbian employees. Disclosing at work and working for an organization perceived to be more gay supportive was related to higher job satisfaction and lower job anxiety. Reactions of coworkers to gay or lesbian work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
539
2
9

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(567 citation statements)
references
References 50 publications
17
539
2
9
Order By: Relevance
“…Those who were out also had lower conflict between work and home, lower role ambiguity, and lower role conflict (Day & Schoenrade, 1997). Decisions about disclosure are related to perceptions of the climate for GLBT employees, including perceived managerial and peer attitudes and organizational policies (Griffith & Hebl, 2002;Huffman, Watrous-Rodriguez, & King, 2008;Ragins, 2008).…”
Section: Sexual Orientation As An (Invisible) Aspect Of Diversitymentioning
confidence: 99%
“…Those who were out also had lower conflict between work and home, lower role ambiguity, and lower role conflict (Day & Schoenrade, 1997). Decisions about disclosure are related to perceptions of the climate for GLBT employees, including perceived managerial and peer attitudes and organizational policies (Griffith & Hebl, 2002;Huffman, Watrous-Rodriguez, & King, 2008;Ragins, 2008).…”
Section: Sexual Orientation As An (Invisible) Aspect Of Diversitymentioning
confidence: 99%
“…Building on previously conducted research on the perceived organizational climate for lesbian and gay employees and its impact on individuals' workplace behavior Bowen and Blackmon 2003;Driscoll et al 1996;Griffith and Hebl 2002;Lyons et al 2005;Ng et al 2012;Ragins and Joseph 2004;Waldo 1999) this article demonstrates for the first time in a comprehensive way the relationship between concrete organizational diversity practices and psychological climate perceptions, regardless of whether as part of a diversity management strategy or as isolated practices.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to directive 2000/78/EC of the European Council, and makes antidiscrimination guidelines on sexual orientation largely irrelevant for European diversity management practice, as they are, in any case, obligatory, at least in terms of regulating everyday interaction between employees or between employees and supervisors. More generally, it was shown that the feeling of being supported by the employing organization in issues that are related to homosexuality in the workplace (Griffith and Hebl 2002), and especially the experienced support of direct supervisors (Huffman et al 2008), positively affects individuals' job satisfaction. The perception of general compatibility between employee and organization seems to be more relevant for homosexual employees than for heterosexuals (Lyons et al 2005).…”
Section: Sexual Orientation Diversity Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Ragins & Cornwell, 2001) and disclosure at work (e.g. Griffith & Hebl, 2002;Ragins, Singh, & Cornwell, 2007) and sexual risk behaviour among men (e.g. McCoul & Haslam, 2001;Peterson & Bakeman, 2006).…”
Section: The Subject Scriptmentioning
confidence: 99%